2017
DOI: 10.18178/ijmmm.2017.5.2.295
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heat Treatments for Electroless Deposited Ni-B and Ni-W-B Coatings on 7075 Al Alloy

Abstract: Abstract-Electroless

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 12 publications
1
17
0
Order By: Relevance
“…The amorphous precipitates get crystallized above 320ºC . corrosion resistance and wear resistance increased duo to The formation of Ni3P [9][10]. the temperature is important and should be the same in the whole bath that can be done by agitation of the solution .…”
Section: Introductionmentioning
confidence: 99%
“…The amorphous precipitates get crystallized above 320ºC . corrosion resistance and wear resistance increased duo to The formation of Ni3P [9][10]. the temperature is important and should be the same in the whole bath that can be done by agitation of the solution .…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical alloying can be used to overcome this difficulty. In this way, Ni-B intermetallics can be produced which have lower melting degrees than nickel and melting degrees of the pipe [10,11]. Among the nickel and boron, there are many intermetallic phases such as Ni 3 B, Ni 2 B, Ni 4 B 3, and NiB.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of Ni 3 P increases hardness and resistance to wear at the expense of formability and resistance to corrosion. [18][19][20][21] Temperature is another important factor for the properties of Ni-P electroless coatings. It was found that the reductioning agent and the complexing agent in the Ni-P electroless process is dependent on the temperature.…”
Section: Introductionmentioning
confidence: 99%